Demography, Clinical Profile and Outcome of COVID-19 Patients in the east-southern region of Bangladesh - Hoque, Mohammad Izazul; Amin, Al; Hafsa, Najnin Jahan; Akter, Roksana; Shaha, Pinki; Roy, Utshab; Hasan, Md Nazmul; Saem, Abu Mohammad (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Introduction: In Bangladesh, the first confirmed case of COVID-19 was detected on March 8 2020, about 3 months after the initial outbreak in late December 2019 in Wuhan, China. Both affected cases and deaths have increased exponentially during this global pandemic. Demographic and clinical data on COVID-19 in Bangladesh is still deficient. Our study aims to evaluate the demographic, clinical profile and outcome of COVID-19 Patients in the east-southern region of Bangladesh. Methodology: It was a cross sectional study. All RT-PCRpositive patients who tested in the RT-PCR lab of Comilla Medical College on 10 days of each month from July to December 2020 were included in this study. Ten days in each month were selected by lottery. After getting the verbal consent, selected patients were interviewed over the telephone by the investigator team, and their information was recorded accordingly in a preformed data sheet. Results: A total of 606 COVID-19 RT-PCR-positive patients were interviewed. The mean age was 40.39 ± 15.42 years; 62.8% were male, and 17.3% of patients had positive contact history with COVID-19 patients. Predominant presenting symptoms were fever (71.8%), cough (41.3%), breathlessness (22.8%), fatigue (18.3%), anorexia (26%) and diarrhea (4.1%). Hypertension (13.1%), diabetes mellitus (16.1%), ischemic heart disease (IHD) (2.8%) and chronic kidney disease (CKD) (0.4%) were frequent comorbidities. 72% of the patients were mild, 16% moderate , 7% severe, and 5% critically ill. 78% took home treatment and 5% were in ICU. 97.2% recovered and 2.8% died. Older age (p= 0.001), male sex (p= 0.007), smoking (p= 0.001), breathlessness (p=0.001) and presence of comorbidities (p= < 0.05) were significantly associated with mortality. 33.8% had post- COVID symptoms, including fatigue 26.7% and shortness of breath 13.2%. Conclusion: Younger age groups were more affected than older age groups. Majority of the patients did not have a history of contact with COVID-19 patients. Most of the patients had mild symptoms. About one fourth were hospitalized, among them 5% got treatment in ICU. Most of the patients recovered, and 2.8% died. Death was more common in patients with multiple comorbidities. One third of recovered patients had post-COVID symptoms. J Bangladesh Coll Phys Surg 2023; 41(4): 298-304